Real magnetic stripping method in unexploded ordnance detection and remediation – a case study from Rohožník military training range in SW Slovakia - PAŠTEKA, Roman; HAJACH, Miroslav; BRIXOVÁ, Bibiana; MIKUŠKA, Ján; STANLEY, John (Contributions to Geophysics and Geodesy, 2021)
In this contribution we present results from a case-study, which was performed in collaboration between geophysicists and explosive ordnance disposal technicians at the Rohožník military training range in SW Slovakia. The aim of this study was to locate a deep-penetrated unexploded Mk-82 aerial bomb using high-definition digital magnetometry. The location where this bomb had entered the ground was known but its final position needed to be determined so that a safe excavation and disposal could be conducted. However, the detection of this unexploded ordnance object was complicated by the presence of intense magnetic interference from a number of near surface ferrous items including non-explosive test bombs, fragmentation and other iron junk. These items contributed a localised, high amplitude of magnetic clutter masking any deeper source. Our strategy was to approach the problem in three stages. First, we used magnetic data to locate the near surface items. After the detection and before the excavation of the searched objects, two quantitative interpretation methods were used. These involved an optimised modelling of source bodies and the application of a 3D Euler deconvolution. Both methods yielded acceptable results, but the former was found to be more accurate. After the interpretation phase, many of the items were then safely excavated and removed individually. A second magnetic mapping was then performed and from this data which was now significantly less cluttered, we were able to identify but not quantify, two deep source items and to confirm that all remaining near surface items were significantly smaller in size than a Mk-82 bomb. As the remaining near surface sources were interpreted as being contained within the surface one metre of soil and being small they could be assured to be non-explosive, it was considered most practical to mechanically excavate and remove this soil and the remaining objects contained.